PERLINDUNGAN HUKUM TERHADAP HAK KEKAYAAN INTELEKTUAL PADA INDUSTRI KONTEN DIGITAL - Devi, Ni Kadek Alvina; Sudirga, I Made (Jurnal Hukum Mahasiswa, 2024)
Legal protection of intellectual property rights (IPR) in the digital era is important because of the increasing economic activity and innovation carried out online. The aim of this research is to understand the challenges and solutions in protecting IPR in the digital era and to evaluate the effectiveness of existing legal instruments. The method used is descriptive and qualitative analysis based on the latest literature and legal regulations related to IPR in the digital era. The research results show that the digital era poses new challenges in IPR protection such as copyright infringement, identity theft and content piracy. However, there have been efforts to address these challenges through regulations such as the Copyright Act and the WIPO Convention.